The evolution of International business 1800-1945. Volume 4 : France and the economic development of Europe, 1800-1914 - Cameron, Rondo E. (London ; New York : Routledge, 2000)
Introduction. Determinants of economic progress. Sinews of growth: credit and transport. Case histories of development and disappointment. Epilogue and conclusion.
Keywords: Economics; Europe; Europe -- Economic conditions; France -- Foreign economic relations; France -- Economic conditions